Amuzja Witkacego - Bocheński, Tomasz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
Witkacy suffered from amusia as a child and as an adult person. He was seriously inter-ested in music only for little longer than twenty years (1890–1914?). He wrote his main works as amusic. The relation between amusia and metaphysical feelings may suggest that Witkacy wrote dramas and created painting compositions in order to evoke lost strangeness of being. Amusia could have also been the reason of Witkacy ambiguity – he was defending and degrading high art at the same time.